KEMAMPUAN SPASIAL MAHASISWA MENGGUNAKAN GEOGEBRA PADA IRISAN KERUCUT - Revi Lestari Pasaribu; Dede Suratman (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to describe the spatial ability of student to use GeoGebra in solvinf space geometry problems, especially in conical slices. The specific objective of this study are a) explaining the fluency of student using GeoGebra in solving problem in cone slices in the space analytical geometry lecture. The qualitative research method provides problems related to cone slices, which are then solved using GeoGebra. The research subjects are mathematics education students majoring in Mathematics and Natural Sciences Education (PMIPA) Faculty of Teacher and Education (FKIP) Tanjungpura University (Untan). They are studying spatial analytical geometry in the 2020/2021 year totaling 18 students. In this study, the instrument used was an instrument in the form of cone slice questions with its completion using GeoGebra; the instrument was designed to see the spatial ability of students based on five indicators. Through this research, the results were obtained that students fluency in using GeoGebra, in general is quite good, as well as students spatial abilities.